Neuronal and glial factors contributing to sex differences in opioid modulation of pain. (January 2019) - Averitt, Dayna; Eidson, Lori; Doyle, Hillary; Murphy, Anne
Abstract Morphine remains one of the most widely prescribed opioids for alleviation of persistent and/or severe pain; however, multiple preclinical and clinical studies report that morphine is less efficacious in females compared to males. Morphine primarily binds to the mu opioid receptor, a prototypical G-protein coupled receptor densely localized in the midbrain periaqueductal gray. Anatomical and physiological studies conducted in the 1960s identified the periaqueductal gray, and its descending projections to the rostral ventromedial medulla and spinal cord, as an essential descending inhibitory circuit mediating opioid-based analgesia. Remarkably, the majority of studies published over the following 30 years were conducted in males with the implicit assumption that the anatomical and physiological characteristics of this descending inhibitory circuit were comparable in females; not surprisingly, this is not the case. Several factors have since been identified as contributing to the dimorphic effects of opioids, including sex differences in the neuroanatomical and neurophysiological characteristics of the descending inhibitory circuit and its modulation by gonadal steroids. Recent data also implicate sex differences in opioid metabolism and neuroimmune signaling as additional contributing factors. Here we cohesively present these lines of evidence demonstrating a neural basis for sex differences in opioid modulation of pain, with a focus on the PAG as a sexually dimorphic core of descending opioid-induced inhibition and argue for the development of sex-specific pain therapeutics.